Microstructure of nanocrystalline TiO2 films produced by electrophoretic deposition on Ti-6Al-7Nb alloy - Boccaccini, Aldo R.; et al. (Surface & Coatings Technology, 2007)
Nanocrystalline TiO2 powders were electrophoretically deposited on the surface of Ti-6Al-7Nb alloy substrate. Post heat treatment at 850 °C was performed to improve the adhesion strength of the coating. The microstructure of the coating and substrate has been examined by light microscopy, scanning electron microscopy, analytical TEM methods (SAED, EDS) and X-ray diffraction. TEM investigations of cross-section thin foils allowed for detailed analysis of the coating microstructure. The TiO2 film exhibited a nanocrystalline structure. SAED and XRD analyses show that the as-deposited nanocrystalline TiO2 films exhibited anatase and rutile phase. The micromechanical properties (microhardness, Young's modulus) were measured. The results obtained show that TiO2 films have low hardness and Young's modulus. During scratch tests any flaking or fracture was observed. © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.micros
Keywords: Electrophoretic deposition; Titanium alloy; Titanium oxide; Transmission electron microscopy